A new technique for driven piles instrumentation - Ali, F.H.; Lee, S.K. (Amer Soc Testing Materials, 2010)
Currently, strain gauges are normally used to monitor the strain development in the pile during static pile load test. For concrete spun pile, the technique used either by incorporating high temperature-resistant strain gauges into the heat-cured production process of the spun piles or by installing an instrumented steel pipe into the hollow core of the spun piles followed by cement grout infilling. The former is extremely unpopular due to high cost of these gauges and the uncertainty over their ability to survive the pile production and driving processes. The shortcoming of the other technique is the infilling of cement grout substantially alters the structural properties of the piles, thus, rendering their load-response behaviour significantly different from that of the actual working piles. This paper highlights the application of a method, recently developed by the authors, which uses retrieval sensors instead of strain gauges which have to be sacrificed in every test. The method is particularly useful to monitor loads and displacements at various levels along the pile shaft and toe of instrumented piles. Results of field tests show high quality, reliable, and consistent data, clearly far exceeding the capability of both conventional methods of using strain gauges.